Efektivitas Model Pembelajaran Learning Cycle 7e Bervisi SETS (Science, Environment, Technology, And Society) untuk Meningkatkan Kemampuan Berpikir Kritis Siswa - Sri Hariyati; Arif Maftukhin; Sriyono Sriyono (Radiasi : Jurnal Berkala Pendidikan Fisika, 2018)
Research has been conducted to find out the effectiveness of the Learning Cycle 7E learning model with SETS (Science, Environment, Technology, and Society) vision to improve the critical thinking skills of class X students of SMA Negeri 11 Purworejo. This research is a quasi-experimental study with a nonequivalent control group design. The population in this study were all grade X students of SMA Negeri 11 Purworejo consisting of 5 classes totaling 160 students. The research sample consisted of 62 students, namely 31 students of class X-1 as an experimental class and 31 students of class X-2 as a control class. Sampling using a purposive sampling technique and data collection is done by interview, observation, and test methods. Data analysis techniques with a t-test with a significance level of 0.05. The results showed that the average critical thinking ability of the experimental class students was 80.3% and the gain was 0.63 with the moderate category. Assessment of the condition of classroom facilities was obtained 84.6% with the category meets the standard. The mean of the learning performance of teachers at four meetings namely 3.88 was declared very good with an average Percentage Agreement (PA) 98.92% declared very reliably, while the average implementation of student learning at four meetings namely 3.85 was stated very well with the average Percentage Agreement (PA ) 98.00% were declared very reliable. Based on the hypothesis test results obtained tobs = 3,660 with ttable = 2,000 and critical area dB = 60 {t / t -2,000 or t> 2,000}, which means that H0 is rejected (tobs ∉ DK) so that the Learning Cycle 7E learning model SETS vision is effective to improve critical thinking skills. Based on these results, the Learning Cycle 7E learning model SETS vision is effective to improve students' critical thinking skills.